Hollow NiSe Nanocrystals Heterogenized with Carbon Nanotubes for Efficient Electrocatalytic Methanol Upgrading to Boost Hydrogen Co‐Production - Zhao, Bin; Liu, Jianwen; Xu, Chenyu; Feng, Renfei; Sui, Pengfei; Wang, Lei; Zhang, Jiujun; Luo, Jing‐Li; Fu, Xian‐Zhu (Advanced functional materials, 2021)
Electro‐oxidative organic upgrading, as an ideal alternative to sluggish oxygen evolution reaction (OER) performance, can effectively decrease energy consumption to boost hydrogen evolution reaction (HER) performance. However, developing highly active electrocatalysts for long‐term durable organic upgrading with high selectivity at large and steady current density remains challenging. Herein, hollow NiSe nanocrystals heterogenized with carbon nanotubes (h‐NiSe/CNTs) are fabricated via a facile one‐pot approach. The highly dispersed h‐NiSe/CNTs 3D network can efficiently facilitate rapid mass/electron diffusion, thus achieving highly active and long‐term stable electrocatalysis for catalyzing methanol to value‐added formate at high and steady current density (≈345 mA cm−2) with high Faradaic efficiency (>95%). This reaction replaces sluggish OER performance to reduce the energy consumption for boosting H2 generation by six times. The critical active species and methanol activation mechanism are systematically studied using X‐ray photoelectron spectroscopy, X‐ray absorption fine structure analysis, in situ Raman, and density functional theory calculations, indicating that the non‐ignorable SeOx collaborated with in situ formed NiOOH species can synergistically modulate the d band center to achieve an optimal adsorption for methanol selective oxidation and suppress the further oxidation to CO2, thus leading to active and stable electrolysis for producing value‐added formate with high selectivity and co‐generating H2 with less energy consumption. Hollow NiSe nanocrystals/carbon nanotubes nanoheterostructures are synthesized as highly active and durable electrocatalysts for long‐term methanol selective upgrading conversion to value‐added formate at large and steady current density (≈345 mA cm−2) with a high Faradaic efficiency (>95%), simultaneously replacing sluggish OER performance to boost H2 generation with lower energy costs.